2020
DOI: 10.1002/ijgo.13511
|View full text |Cite
|
Sign up to set email alerts
|

In utero antiretroviral exposure and sociodemographic characteristics on neurodevelopment of HIV‐exposed uninfected children versus HIV‐unexposed uninfected healthy children in Malawi

Abstract: Background To evaluate mental development index (MDI) and psychomotor development index (PDI) scores of HIV‐exposed uninfected (HEU) children by timing of in utero antiretroviral treatment (ART) initiation (Option B+) and sociodemographic characteristics compared with HIV‐unexposed uninfected (HUU) children in Mzuzu, Malawi. Methods One hundred HEU children and 100 HUU children aged 2–30 months were recruited. The differences in MDI and PDI scores between HEU and HUU children were tested by Student's t test, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
1
0
0
Order By: Relevance
“…Specifically, we observed that compared to VDS pre-adolescents, VDD peers had elevated ASD, ADHD, and EBD as well as functional impairment probability scores over 12 months follow-up. Our findings are consistent with previous studies associating VDD in children with increased risk of ASD [1,28,29,45,46] and ADHD [30][31][32][33]. A multinational study of VD supplementation vs. placebo among adults from the United States and Norway found that the VD-supplemented group demonstrated greater stress resiliency [36] and neuropsychological performance over the cold winter months compared to the placebo group.…”
Section: Discussionsupporting
confidence: 92%
“…Specifically, we observed that compared to VDS pre-adolescents, VDD peers had elevated ASD, ADHD, and EBD as well as functional impairment probability scores over 12 months follow-up. Our findings are consistent with previous studies associating VDD in children with increased risk of ASD [1,28,29,45,46] and ADHD [30][31][32][33]. A multinational study of VD supplementation vs. placebo among adults from the United States and Norway found that the VD-supplemented group demonstrated greater stress resiliency [36] and neuropsychological performance over the cold winter months compared to the placebo group.…”
Section: Discussionsupporting
confidence: 92%